Pengembangan Sistem Informasi Manajemen Sekolah Terintegrasi untuk Digitalisasi Administrasi - Surya Arnawa Ida Bagus Ketut; Ida Ayu Gede Wiwik Purnamayanti (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The rapid advancement of the Industrial Revolution 4.0 and Society 5.0 era has driven significant digital transformation across various sectors, including education. Schools are expected to adopt integrated information systems to improve efficiency, data accuracy, and transparency in academic administration. However, many schools, particularly in rural areas such as Tabanan Regency, Bali, still rely on manual processes involving paper records and spreadsheets. This situation often leads to inefficiencies, data inaccuracies, limited accessibility, and vulnerability to document loss or damage. SMA Negeri 1 Marga is one such school that continues to manage core administrative tasks—such as student data, grading, and report card preparation—manually. To address these challenges, this study aims to develop an Integrated School Management Information System (SIMS) that supports the digitalization of administrative processes and improves overall school management.The research adopts a Research and Development (R&D) approach using the System Development Life Cycle (SDLC) with the Prototype model to ensure iterative feedback from users. The system was implemented using PHP for the backend, MySQL for the database, and HTML, CSS, and JavaScript for the front end. Blackbox Testing was conducted to evaluate the system’s functionality, involving representative users: administrators, teachers, students, and parents. The test results show that most modules, including Login, User Data, Master Data, Teacher and Student Dashboards, Parent Dashboard, and Announcements, achieved a 100% success rate. Only minor issues were found in the Schedule module (87.5%) and Student Grades module (91.7%), resulting in an overall success rate of 97.5%. These findings indicate that the developed SIMS is highly suitable for implementation, effectively addressing the current challenges faced by the school. The system significantly improves efficiency, enhances data accuracy, and ensures transparency among all stakeholders, demonstrating the potential of digital solutions to transform school administration in similar educational environments.